Diversification and systemic risk: A financial network perspective - Rüdiger Frey; Juraj Hledik (Risks, 2018)
In this paper, we study the implications of diversification in the asset portfolios of banks for financial stability and systemic risk. Adding to the existing literature, we analyse this issue in a network model of the interbank market. We carry out a simulation study that determines the probability of a systemic crisis in the banking network as a function of both the level of diversification, and the connectivity and structure of the financial network. In contrast to earlier studies we find that diversification at the level of individual banks may be beneficial for financial stability even if it does lead to a higher asset return correlation across banks.
Keywords: G21; G28; 330; systemic risk; financial network; diversification